The Effect of Profitability on Financial Distress with Leverage as a Moderating Variable in Pharmaceutical Sub-Sector Companies Listed on the IDX from 2018-2020 - Irwin Gunawan Sahala Subiyanto; Harlyn Lindon Siagian (Budapest International Research and Critics University, 2022)
Financial distress is a condition where management is unable to overcome financial problems that cause a decrease in financial performance successively before the company is declared bankrupt. This research has something to be achieved. This study aims to determine the effect of profitability on financial distress with the moderating variable leverage, and to determine whether the company went bankrupt. The sample used in this study were 12 pharmaceutical sub-sector companies listed on the Indonesia Stock Exchange (IDX) 2018-2020. The analytical method used is descriptive statistical method with the Moderated Regression Analyze analysis tool. The results of this study indicate that there is a significant negative effect of the ROA variable on bankruptcy prediction. The DAR variable is able to moderate the relationship between ROA and bankruptcy. By using the Altman Z-Score model. The solution that companies can take to anticipate a decline in financial performance is discipline in paying short-term debt and efficiently using debt capacity to get very large profits from their obligations to avoid financial difficulties.